2021
DOI: 10.2147/orr.s306316
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Insall-Salvati Ratio Among the Vietnamese Population: Application for Diagnosis of Patellar Malalignment

Abstract: An abnormal patellar position has been proven to be associated with anterior knee pain and several other conditions that affect the patellofemoral joint. The purpose of this study was to determine the incidence of patella alta and patella baja and the applicability of the normal range of the Insall-Salvati ratio in the Vietnamese population. Methodology: Magnetic resonance imaging (MRI) was used to examine 455 Vietnamese subjects' knees. The Insall-Salvati ratio-the ratio of patellar ligament length (LL) and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
(35 reference statements)
1
3
1
Order By: Relevance
“…Several studies showed no significant differences in IS ratio between gender. 16 On the other hand, our study showed a significantly higher IS ratio in males compared to females, which is probably due to a higher percentage of male participants compared to females (146 vs 56). Although the mean IS ratio was statistically significant, the clinical value was not clinically significant (1.02 ± 0.13 vs 0.94 ± 0.16).…”
Section: Discussioncontrasting
confidence: 50%
“…Several studies showed no significant differences in IS ratio between gender. 16 On the other hand, our study showed a significantly higher IS ratio in males compared to females, which is probably due to a higher percentage of male participants compared to females (146 vs 56). Although the mean IS ratio was statistically significant, the clinical value was not clinically significant (1.02 ± 0.13 vs 0.94 ± 0.16).…”
Section: Discussioncontrasting
confidence: 50%
“…26 This difference can be attributed to the long-term stretching of the patellar tendon resulting from common activities like squatting and kneeling in certain countries like India, China, Vietnam, and the Middle East. 12,21,27,28 In our study, we observed that the Insall-Salvati ratio is higher in women compared to men, and this difference is statistically significant. The ratio for women and men in our study was 0.99 ± 0.13 and 0.93 ± 0.15, respectively.…”
Section: Insall-salvati Ratiosupporting
confidence: 44%
“… 26 This difference can be attributed to the long-term stretching of the patellar tendon resulting from common activities like squatting and kneeling in certain countries like India, China, Vietnam, and the Middle East. 12 , 21 , 27 , 28 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations